Three-dimensional graphene-supported Ni₃Fe/Co₉S₈ composites : rational design and active for oxygen reversible electrocatalysis - Hu, Xuejiao (2021)
The development of low-cost and efficient electrocatalysts with a bicomponent active surface for reversible oxygen electrode reactions is highly desirable and challenging. Herein, we develop an effective calcination-hydrothermal approach to fabricate graphene aerogel-anchored Ni₃Fe-Co₉S₈ bifunctional electrocatalyst (Ni₃Fe-Co₉S₈/rGO). The mutually beneficial Ni₃Fe-Co₉S₈ bifunctional active components efficiently balance the performance of oxygen reduction and oxygen evolution reactions (ORR/OER), in which Co9S8 promotes the ORR and Ni₃Fe facilitates the OER. This balance behavior has an obvious advantage over that of monocomponent Ni₃Fe/rGO and Co₉S₈/rGO catalysts. Meanwhile, the additional synergy between porous rGO aerogels and Ni₃Fe-Co₉S₈ endows the composite with more exposed active sites, faster electrons/ions transport rate, and better structural stability. Benefiting from the reasonable material selection and structural design, the Ni₃Fe-Co₉S₈/rGO exhibits not only outstanding ORR activity with the high onset- and half-wave potentials (E onset = 0.91 V and E 1/2 = 0.80 V) but also satisfactory OER activity with a low overpotential at 10 mA cm⁻² (0.39 V). Moreover, rechargeable Zn-air cells equipped with Ni₃Fe-Co₉S₈/rGO exhibit excellent rechargeability and a fast dynamic response.